Genetic diversity of 38 insertion–deletion polymorphisms in Jewish populations. (March 2016) - Ferragut, J.F.; Pereira, R.; Castro, J.A.; Ramon, C.; Nogueiro, I.; Amorim, A.; Picornell, A.
Highlights: A database of 38 autosomal indels for populations with Jewish ancestry is provided. Two Sephardic isolates (Chuetas and Crypto-Jews from Bragança) were also studied. The results obtained demonstrated their usefulness for general forensic purposes. Genetic sub-structure in Mediterranean region cannot be discerned with these loci. Specific databases for Jewish populations should be used in the forensic field. Abstract: Population genetic data of 38 non-coding biallelic autosomal indels are reported for 466 individuals, representing six populations with Jewish ancestry (Ashkenazim, Mizrahim, Sephardim, North African, Chuetas and Bragança crypto-Jews). Intra-population diversity and forensic parameters values showed that this set of indels was highly informative for forensic applications in the Jewish populations studied. Genetic distance analysis demonstrated that this set of markers efficiently separates populations from different continents, but does not seem effective for molecular anthropology studies in Mediterranean region. Finally, it is important to highlight that although the genetic distances between Jewish populations were small, significant differences were observed for Chuetas and Bragança Jews, and therefore, specific databases must be used for these populations.